2022
DOI: 10.1371/journal.pone.0273821
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary consumption of highest priority critically important antimicrobials and various growth promoters based on import data in Pakistan

Abstract: Background Antimicrobial resistance (AMR) is a global public health emergency driven by the indiscriminate use of antimicrobial agents in humans and animals. Antimicrobial consumption surveillance guides its containment efforts. In this study, we estimated, for the first time, veterinary consumption of Critically Important Antimicrobials with Highest Priority (CIA-HtP) for Pakistan. Methods The study used an export/import database which provided imports data collected from the Pakistan Customs Authority. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Antibiotic usage has been linked to an increase in resistance in both humans and food-producing animals, making it a critical public health issue. Injudicious use and over-use of antibiotics within and across clinical and agricultural settings provides a favorable environment for the emergence of antibiotic resistant bacteria, causing infections that are difficult to treat (61). The potential health implications of these are significant, as antibiotic resistant bacteria can spread from food-producing animals to (64).…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic usage has been linked to an increase in resistance in both humans and food-producing animals, making it a critical public health issue. Injudicious use and over-use of antibiotics within and across clinical and agricultural settings provides a favorable environment for the emergence of antibiotic resistant bacteria, causing infections that are difficult to treat (61). The potential health implications of these are significant, as antibiotic resistant bacteria can spread from food-producing animals to (64).…”
Section: Discussionmentioning
confidence: 99%
“…Magiri et al 10.3389/frabi.2022.1055507 to be 9.4mg active ingredient/kg biomass (Hillerton et al, 2017). In Pakistan, AMC was found to be 10.05 mg/kg of the cumulative animal biomass, while in sub-Saharan Africa, it was found to be 5.24 ± 1.40 mg/population correction unit (Mouiche et al, 2020;Umair et al, 2022). Studies in Timor-Leste, which is a low and middle income country with a relatively similar agricultural system like Fiji, AMC in food animals was reported to be 0.55 mg/kg after adjusting for animal biomass (Ting et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Given the fact that colistin, a WHO reserve category antibiotic, is identified as one of the possible treatment options for carbapenem resistant infections, its manufacturing for use in food animals and international trade continues unchecked [ 140 ]. In a recent study, we reported veterinary imports of WHO-CIA as pharmaceutical raw materials and growth promoters in worryingly high amounts [ 141 ]. Moreover, the emergence and prevalence of mobile resistance mechanisms for colistin mcr-1 and tigecycline tet (X4) in chickens [ [142] , [143] , [144] ] carries a possible threat of dissemination through food chain.…”
Section: Discussionmentioning
confidence: 99%